Biofilms in Water Hoses of a Meat Processing Environment Harbor Complex Microbial Communities - Voglauer, Eva M.; Zwirzitz, Benjamin; Thalguter, Sarah; Selberherr, Evelyne; Wagner, Martin; Rychli, Kathrin (Frontiers in Microbiology, 2022)
Safe and hygienic water distribution is essential for maintaining product quality and safety. It is known that biofilms alter the appearance and microbial quality of water along the distribution chain. Yet, biofilms in water hoses throughout the food processing environment have not been investigated in detail. Here, microbial communities from water hoses and other environmental sites in contact with water, in addition to the source water itself, were studied in the meat processing environment. Biofilms were present in all water hoses as determined by the presence of bacterial DNA and biofilm matrix components (carbohydrates, extracellular DNA, and proteins). The microbial community of the biofilms was dominated by Proteobacteria, represented mainly by Comamonadaceae and Pseudoxanthomonas. Moreover, genera that are associated with an intracellular lifestyle (e.g. Neochlamydia and Legionella) were present. Overall, the microbial community of biofilms was less diverse than the water microbial community, while those from the different sample sites were distinct from each other. Indeed, only a few phyla were shared between the water hose biofilm and the source water or associated environmental samples. This study provides first insights towards understanding the microbiota of water hose biofilms in the food processing environment.